Genetic characterization of cassava (Manihot esculenta Crantz) cultivars using ISSR molecular marker - Poeaim, S.; Sansanee, S.; Chantaraprasit, T.; Chareonsap, P. P.; Tangthirasunun, N. (My University, 2024)
The genetic diversity of 22 cassava varieties using the inter-simple sequence repeat (ISSR) molecular marker was investigated. Genetic similarity was derived from the matrix of simple similarity coefficients using the unweighted pair group method with arithmetic average (UPGMA). The genetic similarity coefficient ranged from 0.73 to 0.94. The similarity coefficient at 0.73, cluster analysis was clustered to be 22 cassava varieties into two significant groups. The first group was the sweet variety of cassava used for consumption, consisting of Rayong2, Hana-tee and variegated leaves used for decoration. Another group, the bitter variety of cassava used for industry, consisted of Rayong1, Rayong3, Rayong5, Rayong7, Rayong9, Rayong11, Rayong15, Rayong60, Rayong72, Rayong86-13, Rayong90, Kasetsart50, Kasetsart72, Huay Bong60, Huay Bong80, Huay Bong90, Pirun1, Pirun2 and unknown. The sweet and bitter variety contained different levels of cyanide content. So, the ISSR marker might be able characterize two major cassava varieties.
Keywords: Cassava; ISSR; Manihot esculenta; Molecular marker